Distribution of foraging shearwaters relative to inner front of SE Bering Sea - Jahncke, J; Coyle, KO; Zeeman, SI; Kachel, NB; Hunt, GL (Marine Ecology Progress Series, 2005)
We examined the hypothesis that short-tailed shearwaters Puffin us tenuirostris aggregate to forage at the inner front of the SE Bering Sea because of enhanced production there. We tested this hypothesis by comparing primary production, the distribution of euphausiids and the distribution of shearwaters relative to the front during late spring and late summer/early fall of 1997, 1998 and 1999. We found enhanced primary production at the front and offshore of the front during summer but not during spring. Primary production varied between seasons and years. Major differences were related to anomalous conditions in 1997 and 1998. The density of euphausiids was higher at the front and offshore of the front during summer, but there were no differences among regions during spring. Foraging shearwaters aggregated in high densities at the front during summer, but foraged close to shore during spring. At the front, shearwaters foraged on euphausiids Thysanoessa raschii and T. inermis as expected, and on copepods that accumulated in the area. The proportion of zooplankton consumed at the front decreased from summer 1997 to summer 1999, while consumption of sandlance Ammodytes hexapterus at this feature increased. Our results show that, during summer, the inner front supports aggregations of euphausiids and their seabird predators. The means by which the frontal system supports enhanced production and the subseguent trophic transfers is dependent on the availability of nutrients at depth in the frontal region and the aggregation of small zooplankton organisms in this feature. © Inter-Research 2005.